Membentuk Karakter dan Kesadaran Lingkungan melalui Pendidikan Agama Hindu: Tantangan dan Upaya Pengembangan di Era Globalisasi - Sudarsana, I Ketut; Andriyani, Ni Luh Putu Liyana (Jurnal Simki Pedagogia, 2024)
The aim of this research is to find out the teachings that shape character and environmental awareness in Hindu religious teachings. This research uses a qualitative method with a case study approach. The research results reveal that Hindu education provides a solid foundation for people to understand and absorb the teachings of Hinduism in depth. This includes understanding philosophical concepts such as karma (the law of cause and effect), dharma (moral obligation), and moksha (spiritual liberation), as well as various other teachings that help people find the path to perfection. In addition, Hindu religious education encourages spiritual practices such as worship, meditation, and maintaining balance between body, soul, and mind. It helps people grow in positive traits such as patience, wisdom, and inner calm, which are important components of character development. Hindu religious education is very important to instill a sense of love and appreciation in children. Classical Hindu books provide important lessons about the relationship between humans and the universe. Thus, Hindu religious education can be an important pillar in forming a young generation who is ethical, virtuous and cares about the environment. However, to ensure that Hindu religious education is effective in facing the challenges of the times and has a greater positive impact on society as a whole, comprehensive improvement and improvement efforts are needed.